2018
DOI: 10.1080/1357650x.2018.1482906
|View full text |Cite
|
Sign up to set email alerts
|

Relative age effect and left-handedness in world class water polo male and female players

Abstract: Most studies of the relative age effect (RAE) refer to popular sports. In contrast, we examined to what extent the RAE is present in elite water polo players, as well as the association between handedness and RAE. For these purposes, laterality, anthropometry, month of birth, performance and playing position of participants in the 2011, 2013 and 2015 World Championships (623 women, 622 men) were analised. No RAE was observed in the total sample. However, the proportion of male left-handed field players born in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 36 publications
0
21
2
2
Order By: Relevance
“…In this study, the IDs ranged from 1.34 to 2.69 underlined the presence of RAE in all considered team sports. Thus, the present results showed a different pattern in senior Italian context compared to International ones, where RAE was small or negligible as observed in basketball (Delorme et al, 2009; Werneck et al, 2016; López de Subijana and Lorenzo, 2018), rugby league (Till et al, 2010), volleyball (Campos et al, 2016) and water polo at senior level (Barrenetxea-Garcia et al, 2018). On the other hand, it possible that the proportion of players with less than 18 years (overall mean = 12%) in analyzed teams may partially influence the results contradicting previous results in senior teams and in accordance with other studies which describe RAE in European National Teams (Arrieta et al, 2016).…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…In this study, the IDs ranged from 1.34 to 2.69 underlined the presence of RAE in all considered team sports. Thus, the present results showed a different pattern in senior Italian context compared to International ones, where RAE was small or negligible as observed in basketball (Delorme et al, 2009; Werneck et al, 2016; López de Subijana and Lorenzo, 2018), rugby league (Till et al, 2010), volleyball (Campos et al, 2016) and water polo at senior level (Barrenetxea-Garcia et al, 2018). On the other hand, it possible that the proportion of players with less than 18 years (overall mean = 12%) in analyzed teams may partially influence the results contradicting previous results in senior teams and in accordance with other studies which describe RAE in European National Teams (Arrieta et al, 2016).…”
Section: Discussioncontrasting
confidence: 64%
“…Despite the pervasiveness of RAE in youth sport teams, controversial results were found at senior professional level (Delorme et al, 2009; Romann et al, 2018). For example, large RAE was found in soccer (Gonzalez-Villora et al, 2015; Brustio et al, 2018), while small or negligible RAE was observed in other sport teams such rugby league (Delorme et al, 2009; Till et al, 2010; Jones et al, 2018), basketball (Delorme et al, 2009; Werneck et al, 2016; López de Subijana and Lorenzo, 2018), volleyball (Campos et al, 2016) and water polo (Barrenetxea-Garcia et al, 2018). A discrepancy in RAE at senior professional level may also emerge in relation to the countrywide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant unexpected finding was found in the performance analysis by competition level. Although some samples showed an influence of the RAE on competition performance at international level (Williams, 2010 ; Torres-Unda et al, 2016 ; Ibañez et al, 2018 ), interestingly, a similar number of samples and athletes, in which the RAE or RAE reversal did not affect competition performance, was also found (García et al, 2014 ; Karcher et al, 2014 ; Barrenetxea-Garcia et al, 2019 ), especially in the short term. Nevertheless, it should be specified that most of the measurements were collected from competitions in the senior category.…”
Section: Discussionmentioning
confidence: 96%
“…The presence of an RAE has been observed at the senior and youth levels in the following contact team sports: basketball (Arrieta et al, 2016;Werneck et al, 2016), soccer (González-Víllora et al, 2015;Skorski et al, 2016), and handball (Schorer et al, 2009). Contrary, the RAE was not found in other team sports such as rugby (Jones et al, 2018) and water polo (Barrenetxea-Garcia et al, 2018). In line with this, the findings of existing literature on RAE in contact team sports have been controversial so far.…”
Section: Introductionmentioning
confidence: 98%